Mapping brain activity with flexible graphene micro-transistors. (24th February 2017) - Blaschke, Benno M; Tort-Colet, Núria; Guimerà-Brunet, Anton; Weinert, Julia; Rousseau, Lionel; Heimann, Axel; Drieschner, Simon; Kempski, Oliver; Villa, Rosa; Sanchez-Vives, Maria V; Garrido, Jose A
Abstract: Establishing a reliable communication interface between the brain and electronic devices is of paramount importance for exploiting the full potential of neural prostheses. Current microelectrode technologies for recording electrical activity, however, evidence important shortcomings, e.g. challenging high density integration. Solution-gated field-effect transistors (SGFETs), on the other hand, could overcome these shortcomings if a suitable transistor material were available. Graphene is particularly attractive due to its biocompatibility, chemical stability, flexibility, low intrinsic electronic noise and high charge carrier mobilities. Here, we report on the use of an array of flexible graphene SGFETs for recording spontaneous slow waves, as well as visually evoked and also pre-epileptic activity in vivo in rats. The flexible array of graphene SGFETs allows mapping brain electrical activity with excellent signal-to-noise ratio (SNR), suggesting that this technology could lay the foundation for a future generation of in vivo recording implants.